Women's reflections on timing of motherhood: a meta-synthesis of qualitative evidence - Camilla Gry Temmesen; Tove Faber Frandsen; Henriette Svarre-Nielsen; Kathrine Birch Petersen; Jane Clemensen; Heidi Lene Myglegaard Andersen (BMC, 2023)
Plain language summary In many countries, women's age at the birth of their first child has risen markedly, and an increasing number of women do not establish a family until their late-twenties to mid-thirties. This causes risk of couples experiencing fertility problems, as fertility declines with increasing age. Although fertility problems can be caused by various reasons, advanced maternal age is the most frequent cause for women having difficulties achieving pregnancy. In this study, we investigated reflections on timing of motherhood in women who have not yet had children. Through a systematic literature search we identified eight qualitative studies published between 2011 and 2018 that focused on women's reflections on timing of motherhood. The included studies were synthesized using a meta-ethnographic approach. We identified an overall theme 'Timing of motherhood' and four overlapping subthemes: Making a life-changing decision, The right time, Fear of regret, and Plan B. The dilemmas associated with timing of motherhood leave women of reproductive age balancing their priorities and values against a biological deadline for having children naturally or through assisted reproductive technology. Women of reproductive age are aware that they must make a life-changing decision as to if or when to have children, but they consider having children at 'the right time' to be important. Simultaneously, while some women are reluctant to have children for various reasons, they express fear that waiting too long could result in their regretting not having children later in life. Although women of reproductive age express concern about their ability to achieve pregnancy, they have limited focus on the medical risks associated with postponing motherhood, which emphasizes the need for establishing preventive health initiatives to support women of reproductive age in their considerations regarding timing of motherhood.